PENGARUH PROGRAM PELATIHAN FISIK MILITER TERHADAP PENINGKATAN VO2 MAX SISWA PENDIDIKAN PERTAMA TAMTAMA TENTARA NASIONAL INDONESIA ANGKATAN LAUT (STUDI DI PUSLATDIKSARMIL KOBANGDIKAL SURABAYA) - PAMBUKA PUTRA, KUKUH Pambuka (Jurnal Kesehatan Olahraga, 2014)
ABSTRACTPhysical training program used in the DIKMATA TNI AL is a physical training program that will transform a civilian into physical bodily a military man, including the cardiovascular system's ability to transport oxygen. This study aimed to determine whether there are changes in the value of VO2max of DIKMATA TNI AL student and how the changes that occur after a 12-week training program. This research is a quantitative approach with the method of pre-experimental and experimental design using pre-test post-test. The population in this study were DIKMATA students men aged 19-22 years as many as 438 people were divided into four companies, and each company containing 3-4 platoon. The samples used were 1st and 3rd platoons of company A which amounts to 58 students with a sampling technique using simple random sampling. Military physical training includes physical fitness training is done every Tuesday, Wednesday and Friday with the addition of load every period of 1 week; military agility training, combat training, and other training that involves some physical activity in accordance with the educational calendar. Instrument in this study is MFT tests conducted before and after the implementation of the training program. Based on this research, there is a difference between the value of VO2max pre-test and post-test average of 9.8 ml×kg-1×min-1 or 26,9% pre-test value. The analysis shows the influence of military physical training program to increase VO2max of DIKMATA TNI AL Student.Keywords: military physical training, VO2Max, MFT, DIKMATA TNI AL